Effect of blending Huanglongbing (HLB) disease affected orange juice with juice from healthy orange on flavor quality. Issue 1 (June 2015) - Raithore, Smita; Dea, Sharon; Plotto, Anne; Bai, Jinhe; Manthey, John; Narciso, Jan; Irey, Mike; Baldwin, Elizabeth
Abstract: Huanglongbing, or citrus greening disease, progressively damages and ultimately kills citrus trees. While this disease does not affect human health, it is associated with bitter off-flavor for orange juice. The objective of this study was to determine the level of HLB-symptomatic (HLBs) juice (made from fruit symptomatic for the disease, harvested from diseased trees) that can be added to healthy juice (extracted from fruit harvested from healthy trees) so that the off-flavor associated with such juice is not perceived. Varying amounts of Hamlin or Valencia HLBs orange juices were blended with respective healthy juices to make 6.25, 12.5, 25, and 50 mL HLBs/100 mL blends. Chemical and sensorial differences were found for both varieties. HLBs juice had lower soluble solids but higher acidity, and limonin and nomilin levels than healthy juice. However, only about 27% of the panelists were able to recognize taste differences in 25 mL HLBS/100 mL blend and less than 9% could recognize taste differences with 6.25 and 12.5 mL HLBs/100 mL blends. Electronic tongue differentiation of blends supported the chemical and sensory differences. Results showed that adding small amounts of HLBs juice to healthy juice does not compromise taste quality. Highlights: Huanglongbing (HLB) disease of citrus is causing off-flavor in orange juice. Fruit symptomatic for the disease (HLBs) produce the most off-flavored juice. Blending up to 25% HLBs juice in healthy juice does not affect flavor. Sensory panels detected a difference with 25% HLBs in healthy juice. Sensory panels recognized disease-induced off-flavor in a 50% HLBs blend.